2017
DOI: 10.3390/toxins10010007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of the Effect of Periplocoside P from Periploca sepium on Brush Border Membrane Vesicles in Midgut Epithelium of Mythimna separata Larvae

Abstract: Periplocoside P (PSP), a novel compound isolated from Periploca sepium Bunge, possesses insecticidal activity against some lepidopterans, such as Mythimna separata. In M. separata, the brush border membrane vesicles of the midgut epithelium are the initial site of action of periplocosides. We conducted two-dimensional gel electrophoresis and matrix-assisted laser desorption/ionization time of flight/time of flight mass spectrometry analysis to analyze differentially expressed proteins (DEPs) from periplocoside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…8 Quantitative differential proteomics studies have demonstrated that PSP treatment markedly upregulates the expression of V-type adenosine triphosphatase (V-ATPase) in M. separata larvae. 9,10 Enzymatic validation further confirmed the concentrationdependent inhibitory effect of PSP on V-ATPase activity. 9,10 Based on the findings mentioned above, we hypothesized that V-ATPase serves as a target for the insecticidal activity of PSP.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…8 Quantitative differential proteomics studies have demonstrated that PSP treatment markedly upregulates the expression of V-type adenosine triphosphatase (V-ATPase) in M. separata larvae. 9,10 Enzymatic validation further confirmed the concentrationdependent inhibitory effect of PSP on V-ATPase activity. 9,10 Based on the findings mentioned above, we hypothesized that V-ATPase serves as a target for the insecticidal activity of PSP.…”
Section: Introductionmentioning
confidence: 73%
“…9,10 Enzymatic validation further confirmed the concentrationdependent inhibitory effect of PSP on V-ATPase activity. 9,10 Based on the findings mentioned above, we hypothesized that V-ATPase serves as a target for the insecticidal activity of PSP.…”
Section: Introductionmentioning
confidence: 73%
“…They speculated that periplocoside P adjusted the transport mechanisms at the apical membrane of the midgut epithelial cells by inhibiting the V-type H + ATPase [194]. In addition, the V-type ATPase A subunit in the midgut epithelium might be regarded as the target binding site of periplocosides, which provided preliminary evidence for the mode of action of periplocosides [195]. Furthermore, aminopeptidases N and N3 of the midgut epithelium cells of M. separata larvae were extrapolated as potential targets of periplocoside E ( 47 ) by affinity chromatography [196].…”
Section: Biological Activitiesmentioning
confidence: 99%
“…23 Additionally, further elaboration of these periplocosides' mode action has been conducted, with results showing that periplocosides could activate protease from the midgut of M. separata after being fed to pests. [24][25][26][27] Notably, it has also been reported that the crude fraction F3-28 made of various periplocosides form PSRB could not only activate protease but it also activated tryptase in vivo. 28 These studies indicated periplocosides could affect mainly digestive enzymes in vivo.…”
Section: Introductionmentioning
confidence: 98%
“…Periplocoside X (PSX) was used as a botanical pesticide against workers of the red imported fire ants (LD 50 = 0.116 mg/mL) 23 . Additionally, further elaboration of these periplocosides' mode action has been conducted, with results showing that periplocosides could activate protease from the midgut of M. separata after being fed to pests 24–27 . Notably, it has also been reported that the crude fraction F3‐28 made of various periplocosides form PSRB could not only activate protease but it also activated tryptase in vivo 28 .…”
Section: Introductionmentioning
confidence: 99%